GENOMES OF VIRAL ISOLATES DERIVED FROM DIFFERENT MOSQUITOS SPECIES - Sadeghi, Mohammadreza (Virus Res, 2017)
Eleven viral isolates derived mostly in Aedes cells from mosquito pools collected in Southeast Asia and the Americas between 1966 and 2014 contained particles with electron microscopy morphology typical of reoviruses. Metagenomics analysis yielded the near complete genomes of three novel reoviruses, Big Cypress orbivirus, Ninarumi virus, and High Island virus and a new tetravirus, Sarawak virus. Strains of previously characterized Sathuvarachi, Yunnan, Banna and Parry’s Lagoon viruses (Reoviridae), Bontang virus (Mesoniviridae), and Culex theileri flavivirus (Flaviviridae) were also characterized. The availability of these mosquito virus genomes will facilitate their detection by metagenomics or PCR to begin to determine their geographic range, extent of host tropism, and possible association with arthropod or vertebrate disease.